Experimental study on feedback control of vortex shedding from a cylinder at low Reynolds numbers - Tao, Jin Sheng. (2009)
This thesis describes the experimental study on the suppression of vortex shedding from circular cylinders at low Reynolds numbers by using feedback control techniques. The experiments were performed in a recirculating water channel. Signals picked up by hot-film probes at the wakes of cylinders were used to produce feedback perturbations which were introduced into the wake in two ways. One way was to oscillate the cylinder in the transverse direction to the flow, which was called external excitation; the other was to generate perturbation inside the cylinder and introduce them locally into the flow through a thin slit on the cylinder surface, which was called internal (local) excitation. Flow visualisation was applied in the experiments to assess the effects of the feedback control on wakes of cylinders.